Free vibration analysis of composite laminated beams with curvilinear fibers via refined theories. Issue 6 (28th February 2022) - Daraei, Behnam; Shojaee, Saeed; Hamzehei-Javaran, Saleh
Abstract: In this article, free vibration finite element analysis of variable stiffness composite laminate (VSCL) beams is carried out. The variable stiffness of laminated beams is acquired by using laminates with curvilinear fibers instead of straight fibers. The analysis is based on the higher-order theories that have been presented by Carrera Unified Formulation (CUF). Equivalent Single Layer (ESL) model, which is independent of the number of constitutive layers, has been utilized to consider a number of unknown variables. Several numerical results for the analysis of VSCL beams are presented and the effect of the fiber orientation angle and various boundary conditions on the natural frequencies are demonstrated.